A taxonomic review of Paramblynotus Cameron, 1908 in China, with descriptions of five new species (Hymenoptera: Cynipoidea: Liopteridae) - Dong, Ying-Ying; Liu, Zhiwei; Wang, Yi-Ping; Chen, Xue- Xin (Zootaxa, 2018)
Five new species of the genus Paramblynotus Cameron, 1908, are herein described from China: Paramblynotus anjiensis, new species, Paramblynotus qingliangfengensis, new species, Paramblynotus longipetiolus, new species, Paramblynotus magnatus, new species and Paramblynotus nigricaputus, new species. Three additional species, Paramblynotus reticulatus (Kieffer, 1910), Paramblynotus nipponensis Liu, Ronquist & Nordlander, 2007 and Paramblynotus rufipes Liu, Ronquist & Nordlander, 2007 are reported from China for the first time and the distribution of six previously reported species are updated with new collection data. Paramblynotus metatarsis He, 2004 and Paramblynotus tianmushanensis He, 2004 are redescribed. A taxonomic review, distribution map, and a taxonomic key are provided for the 19 known species of Paramblynotus from China.